2019
DOI: 10.1021/jacs.9b02628
|View full text |Cite
|
Sign up to set email alerts
|

Direct Functionalization of White Phosphorus to Cyclotetraphosphanes: Selective Formation of Four P–C Bonds

Abstract: Converting elemental white phosphorus directly into organophosphorus or polyphosphorus is meaningful, challenging and attractive. The ate-complexes of aluminacyclopentadienes 1a,b react with P4 to afford selectively the cyclotetraphosphanes 2a,b featuring four newly formed P–C bonds and a planar square cyclo-P4 ring. Density functional theory calculations show that the conversion of tetrahedral P4 to planar cyclo-P4 moiety undergoes through an unexpected 1,1-P-insertion/Diels–Alder reaction/isomerization casca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…The C1‐C2‐C3‐C4 moiety in D retains the diene character, as suggested by the interatomic distances of the C1=C2 double bond (1.38 Å), C2−C3 single bond (1.52 Å), and C3=C4 double bond (1.36 Å). It is also noted that three P atoms in D interact with the Lu complex moiety to stabilize the species, which is clearly distinct from the unstable charge‐separated species in the Al system, in which only one P atom interacts with the Al moiety . This is ascribed to the stronger coordination capability of Lu than Al.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The C1‐C2‐C3‐C4 moiety in D retains the diene character, as suggested by the interatomic distances of the C1=C2 double bond (1.38 Å), C2−C3 single bond (1.52 Å), and C3=C4 double bond (1.36 Å). It is also noted that three P atoms in D interact with the Lu complex moiety to stabilize the species, which is clearly distinct from the unstable charge‐separated species in the Al system, in which only one P atom interacts with the Al moiety . This is ascribed to the stronger coordination capability of Lu than Al.…”
Section: Resultsmentioning
confidence: 94%
“…To get some insights into the process of P 4 dual functionalization, density functional theory (DFT) calculations on the mechanism were performed. Surprisingly, it is found that the first step for nucleophilic activation of P 4 by lutetacyclopentadiene will yield a charge‐separated intermediate resulting from the cleavage of the adjacent P−P bond (Scheme c,d), representing a very rare example . In addition, to get a full understanding of the novel mode of P 4 dual functionalization, at least three points need to be addressed: i) the selectivity in the process of three P−P bond cleavage and four P−C bond formation; ii) how to trigger the reaction and the intermolecular cooperation between two lutetacyclopentadienes; and iii) the prior formation of either the lutetium cyclo ‐P 3 unit involved in 2 or the phospholyl moiety involved in 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Developing chlorine-free protocols for processing white phosphorus has been an active area of research for decades, 101−105 and exciting new reactions are still emerging. 106 Improvements to the methods for preparing phosphonic acids, 107 alkylphosphines, 108,109 and arylphosphines 110 directly from P 4 have benefited from the generation of carbonbased radicals in situ. The recent stabilization of white phosphorus in activated carbon 111 raises the possibility of decreasing the hazards associated with this pyrophoric intermediate, which is likely to feature in chemical synthesis for some time to come.…”
Section: Lessons From Group 14mentioning
confidence: 99%
“…However, limited by the type of nucleophilic reagents and low selectivity of P−P bond cleavage, the functionalization of P 4 through direct P−C bond formation still has few examples [37][38][39][40][41][42][43][44][45][46]. Our group [47][48][49][50][51][52][53] has focused on P 4 functionalization since 2016, especially in the P−C bond formation. We are committed to developing the reactions of a new type of nucleophiles with P 4 , and directly constructing useful organophosphorus compounds.…”
Section: Introductionmentioning
confidence: 99%